2016
DOI: 10.1016/j.funeco.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological conditions and site characteristics driving edible mushroom production in Pinus pinaster forests of Central Spain

Abstract: a b s t r a c tIntegrating fungal-based ecosystem services into forest management planning and policy-making requires quantitative knowledge of the yields of fungal sporocarps and their environmental drivers. The aim of this study was to predict edible mushroom yield in Pinus pinaster forests of Central Spain, based on a 17-year data series. Two-stage mixed-effects models were used to examine the effect of predictors on mushroom occurrence and yield separately with the aim of providing further insight into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 25 publications
(31 reference statements)
1
27
0
Order By: Relevance
“…In all models, precipitation (i.e., cumulative rainfall and number of rainy days) exhibited a one-month time lag in its correlation with mushroom productivity, that is, it became a significant factor affecting one month before the start of the mushroom season, and ceased to be significant one month before the end of the season. This is in agreement with previous research indicating a one month delay in the effect of rain events on mushroom yield in the Mediterranean (Bonet et al, 2012(Bonet et al, , 2010Martínez de Aragón et al, 2007;Taye et al, 2016).…”
Section: Effect Of Weather and Soil Moisture Variables On Mushroom Ocsupporting
confidence: 93%
See 1 more Smart Citation
“…In all models, precipitation (i.e., cumulative rainfall and number of rainy days) exhibited a one-month time lag in its correlation with mushroom productivity, that is, it became a significant factor affecting one month before the start of the mushroom season, and ceased to be significant one month before the end of the season. This is in agreement with previous research indicating a one month delay in the effect of rain events on mushroom yield in the Mediterranean (Bonet et al, 2012(Bonet et al, , 2010Martínez de Aragón et al, 2007;Taye et al, 2016).…”
Section: Effect Of Weather and Soil Moisture Variables On Mushroom Ocsupporting
confidence: 93%
“…Mushroom yield varies dramatically between years due to variation in the environmental factors that determine the duration of the fruiting season and the frequency of mushroom emergence (Alday et al, 2017;Boddy et al, 2014). Climate arises as the foremost important factor, with precipitation and temperature (and their interaction) having a major impact on mushroom phenology, yield and diversity (Bonet et al, 2012;Büntgen et al, 2015;Kauserud et al, 2008Kauserud et al, , 2012Ogaya and Peñuelas, 2005;Taye et al, 2016). However, the effect of climate on mushroom productivity is further modulated by the combined effect of site and soil characteristics and forest stand structure (Martínez-Peña et al, 2012;de-Miguel et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In a research focused on Tricholoma portentusum emergence, the authors [66] showed that this species required a minimum initial amount of rainfall, followed by appropriate temperatures. Moreover, accumulated precipitation from late summer was found to be a driving factor in the occurrence of edible, marketed and L. deliciosus mushrooms in Pinus pinaster forests in Central Spain [28]. Regarding temperature, [67] found a negative influence between Boletus production and the maximum temperature two weeks before the sampling week.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of mushroom dynamics show the influence of site characteristics (altitude [11], slope, aspect), stand variables (tree species, stand density, stand age [12], basal area [13], dominant height, tree growth [14,15]), soil properties [16,17] and weather conditions (precipitation, temperature [18,19]). Different approaches have been used in mushroom modeling, including correlations [20], stepwise multiple regressions [21], classificatory simple model [22], linear and nonlinear models [23,24], mixed models [13,14,17,18,25,26] or the two-step model approach [27,28]. Most of the models incorporate the stochastic between-plot and between-year structure to account for nested structures in the data [29] and thereby avoid biased standard error estimators of the parameters.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that weather conditions have an impact on mushroom occurrence and productivity. Because water availability in the soil or weather is main reactor for sporacarp formation, mean monthly rainfall, mean temperature, mean monthly evapotranspiration and soil temperature and moisture are strongly important variables for mushroom production (Bonet et al 2010;Bonet et al 2012;Martínez-Peña et al 2012a;De La Varga et al 2013;Kucuker and Baskent 2015;Taye et al 2016;Karavani et al 2018;Castaño et al 2017).…”
Section: Introductionmentioning
confidence: 99%